PENGARUH PENGALAMAN TRAUMATIS TERHADAP KESEHATAN MENTAL SISWA KELAS 8 MTs NEGERI 4 SERANG - Afrilia Nur Fadhila; Desty Endrawati Subroto; Galuh Laily Agustin; Maulida Awwaliya; Nur Sahlami (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to explain the effect of traumatic experiences on mental health. The method used in this research is the literature review method. The sample in this study was taken as much as 8% of the 500 number of 8th grade students of MTs Negeri 4 Serang in the 2024 academic year and obtained a sample of 40 students. Data collection techniques used questionnaires, attitude scales, and tests. Traumatic experiences can have a negative impact on an individual's mental health. Trauma, which can stem from events such as violence, natural disasters, sudden loss, or other life experiences, often leads to prolonged emotional, cognitive, and physical impairment. The results of the analysis of the research data processing on the effect of traumatic experiences on mental health show that the attitude of individuals who have trauma will have a very serious impact on their psychological and emotional development, both in the short and long term.